Residual Study: Testing Jupiter Atmosphere Models Against Juno MWR Observations. Issue 9 (19th September 2020) - Zhang, Zhimeng; Adumitroaie, Virgil; Allison, Michael; Arballo, John; Atreya, Sushil; Bjoraker, Gordon; Bolton, Scott; Brown, Shannon; Fletcher, Leigh N.; Guillot, Tristan; Gulkis, Samuel; Hodges, Amoree; et al.
Abstract: The Juno spacecraft provides unique close‐up views of Jupiter underneath the synchrotron radiation belts while circling Jupiter in its 53‐day orbits. The microwave radiometer (MWR) onboard measures Jupiter thermal radiation at wavelengths between 1.37 and 50 cm, penetrating the atmosphere to a pressure of a few hundred bars and greater. The mission provides the first measurements of Jupiter's deep atmosphere, down to 250 bars in pressure, constraining the vertical distributions of its kinetic temperature and constituents. As a result, vertical structure models of Jupiter's atmosphere may now be tested by comparison with MWR data. Taking into account the MWR beam patterns and observation geometries, we test several published Jupiter atmospheric models against MWR data. Our residual analysis confirms Li et al.'s (2017, https://doi.org/10.1002/2017GL073159 ) result that ammonia depletion persists down to 50–60 bars where ground‐based Very Large Array was not able to observe. We also present an extension of the study that iteratively improves the input model and generates Jupiter brightness temperature maps which best match the MWR data. A feature of Juno's north‐to‐south scanning approach is that latitudinal structure is more easily obtained than longitudinal, and the creation of optimum two‐dimensional maps is addressed in this approach. Key Points: Residual analysis provides a direct method to compare any Jupiter atmosphere model with the MWR observations The iterative residual analysis process generates 2‐D Jupiter maps revealing the deep structures of upper atmosphere features